The role of total productivity on Economic Growth - Elías, Victor (Estudios de Economía, 2016)
This paper aims at assessing the importance of total factor productivity (TFP) on economic growth and at “explaining” TFP growth. The contribution share of TFP growth to GDP growth will be estimated for 96 countries in the period 1950-1987. Additionally, previous estimates covering a longer period, though for fewer countries, will be presented as well. These estimates will be presented along with other sources of economic growth, i.e., traditional labor and capital inputs. A brief discussion will be offered of recent literature attempting to improve on economic growth theory provided by neoclassical growth models, though emphasizing the determinants of TFP growth.